Pemberdayaan Masyarakat Ekonomi Lokal melalui Strategi Manajemen Usaha Ternak Lembu di Desa Patumbak - Ratna Sari Dewi; Irfan Hakim; Fahrul Rozi Tarigan; Salsalliah Albant Triswandi; Meri Meirisa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in supporting the national economy, especially in the agricultural and livestock sectors. Mr. Hanafi's cattle farming business in Patumbak Village is one that plays a very important role in empowering the local economy. However, the limitations of the local community to be able to utilize the potential of resources have caused the progress of cattle sales to be less than optimal. The purpose of this study is to improve the knowledge and skills of cattle farming entrepreneurs through business management strategies, namely marketing strategies. The implementation of activities uses direct socialization and practice methods to cattle farming entrepreneurs, related stakeholders, and local community leaders. It is hoped that through a community empowerment approach in cattle farming business management strategies, it can help the local economy and maximize economic growth.